MODELING STUDY AND NUMERICAL ANALYSIS OF FLEXIBLE PAVEMENT IN SOFT SOIL BASED ON FINITE ELEMENT METHOD - Yonas Prima Arga Rumbyarso; Dohar Sidabutar; Gali Pribadi (CV KULTURA DIGITAL MEDIA, 2026)
Road construction with flexible pavement system on soft clay subgrade faces technical constraints in the form of low bearing capacity, high compressibility, and sensitivity to changes in moisture content, so this study evaluates stress-strain response using finite Element Method (FEM) through two-dimensional modeling (2D) consisting of a layer of clay soil 57 cm thick and a layer of flexible pavement 3 cm thick, with, in three variations of moisture content, namely 19%, 36%, and 53%, where the results of the analysis show that the increase in water content causes an increase in effective stress from 10.57 kN/m2 at 19% to 11.54 kN/m2 at 53%, while the displacement value is relatively stable at around 0.2046 mm, so it can be concluded that although the variation of water content affects the stress distribution, the impact on total deformation is relatively small and flexible pavement is still able to maintain deformation stability in the problematic soil conditions.